DDRE-12. PNOC001 (NCT01734512): A PHASE II STUDY OF EVEROLIMUS FOR RECURRENT OR PROGRESSIVE PEDIATRIC LOW-GRADE GLIOMAS (pLGG). (9th November 2020) - Mueller, Sabine; Aboian, Mariam; Nazemi, Kellie; Gauvain, Karen; Yoon, Janet; Minturn, Jane; Leary, Sarah; AbdelBaki, Mohamed; Goldman, Stewart; Elster, Jennifer; Resnick, Adam; Molinaro, Annette; et al.
Abstract: OBJECTIVE: To estimate the 6-month Progression Free Survival (PFS6) associated with everolimus for progressive/recurrent pLGGs and to determine if activated PI3K/Akt/mTOR pathway as measured by positive phosphorylated-ribosomal protein S6 (p-RPS6) status was associated with response. METHOD: Patients 3–21 years of age with recurrent or progressive pLGG were enrolled. Everolimus was administered orally at 5 mg/m 2 daily. Tissue availability for molecular analysis was mandatory. Immunohistochemistry (IHC) for p-RPS6 was performed centrally. An adaptive Simon two-stage design was employed based on p-RPS6 status. Based on results of the first stage, enrollment in the second stage was either limited to pathway activated patients or open to all subjects. RESULTS: From December 2012 to July 2019 a total of 65 subjects enrolled [median age 9 years (range 3–19); 43% female]. As of December 15, 2019 median number of treatment cycle is 8 (range 1–24); 7 patients remain on treatment. Toxicity profile is similar to published reports with rash and elevated lipid profiles as most common adverse events. PFS6 for the entire cohort is 63%; PFS6 is 64% for the activated and 61% for the non-activated patients. Central imaging review (n=52) revealed 1 partial response, 1 complete response, 33 stable disease, and 17 progressive disease at the end of study treatment. Initial molecular analysis identified BRAF alterations in 35/65 patients. CONCLUSION: Everolimus is well tolerated and active in a subset of pLGGs. Ongoing analyses will assess predictive biomarkers of response and will be reported at the meeting.